1811 Md. Laws 465 - (:unkn) unknown (My University, 1809)
§ 4: Prohibited carrying any pistol, hanger, cutlass, bludgeon, or other offensive weapon with intent to feloniously assault any person, or to be found in any dwelling house, warehouse, stable, or outhouse, garden, or area of a house with intent to steal goods or chattels.
Keywords: CARRY - INTENT TO COMMIT CRIME